A Brief Study on E-Commerce (International Journal of Innovative Research in Computer Science & Technology, 2022)
Internet shopping is now a sea change that  has implications with both consumers and advertisers.  Digital transformation will played a great role as in  upcoming easy access to financial divisions and business  services in a rising economy. To combat deceptive  conduct, the rising use of smart mobile operators and the  World Wide Web as a niche product for exchange of goods  and services and foreign investment needs a stronger  attention on t s security. The advances in internet  technology has created havoc in almost every element of a  lives. E-commerce has a lot of benefits that boost customer  — and give conveniences in any place and enabling a company to get a higher market share. As a consequence  of extensive internet usage, e-commerce has risen in  popularity, and companies, particularly continue, and are  rapidly moving to this option as a differentiating strategic  framework. This paper discusses about E-commerce, E commerce providers, Benefits, and Challenges. This paper  can be used by researchers for further study in E commerce in future.
Keywords: Business; E-Commerce; Internet; Market; Social Media